2010
DOI: 10.1111/j.1464-410x.2009.08913.x
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes but not metabolic syndrome is associated with an increased risk of lower urinary tract symptoms and erectile dysfunction in men aged <45 years

Abstract: metabolic syndrome with LUTS and ED was also evaluated. RESULTSThe mean ( SD , range) age of the patients was 38.9 (6.1, 20-45) years and the mean duration of diabetes was 2.8 (3.1, 0.5-20) years. Compared with controls, men with T2DM had a significantly mean ( SD ) higher IPSS, of 6.1 (5.8) vs 4.1 (4.6) ( P < 0.001), an increased of odds ratio (95% confidence interval) of having moderate to severe LUTS of 1.78 (1.12-2.84) ( P = 0.01), greater voiding volume of 376 (177) vs 326 (102) mL ( P = 0.04), a worse II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…The role of Met S components including WC, HDL, triglycerides, and diabetes on the risk of having moderate-to-severe LUTS have been reported [38919293949596]. More specifically, decreasing T levels have been associated with altered release of adenosine triphosphate (ATP) and acetylcholine (ACh) responsiveness to stretch, micturition reflex, and functional factors like bladder capacity [919798].…”
Section: Metabolic Syndrome Testosterone Deficiency and Pathophysiomentioning
confidence: 99%
“…The role of Met S components including WC, HDL, triglycerides, and diabetes on the risk of having moderate-to-severe LUTS have been reported [38919293949596]. More specifically, decreasing T levels have been associated with altered release of adenosine triphosphate (ATP) and acetylcholine (ACh) responsiveness to stretch, micturition reflex, and functional factors like bladder capacity [919798].…”
Section: Metabolic Syndrome Testosterone Deficiency and Pathophysiomentioning
confidence: 99%
“…A number of large high-quality studies have demonstrated the association of hyperglycemia and insulin resistance with LUTS [19, 32, 33]. In the past few years, multiple population-based reports linking diabetes with LUTS have been reported [7, 27, 31, 34•, 35, 36]. In the previously mentioned cohort from Michigan, Sarma et al found in a model adjusted for age and race at baseline men with diabetes without medication were more likely to report irritative symptoms (odds ratio (OR) 95 % confidence interval (95 % CI) 2.04 (1.08–3.86)) than men with diabetes on medications (OR 95 % CI 1.46 (1.02–2.08)) or men without diabetes (reference group).…”
Section: Hyperglycemia Insulin Resistance and Lower Urinary Tract Smentioning
confidence: 99%
“…Patients with diabetes were more likely to have irritative then storage symptoms. In a case-control cohort of Taiwanese men <45, those with diabetes compared to the control group had worse overall International Prostate Symptom Score (IPSS) (6.1 versus 4.1, p <0.001), worse storage (2.7 versus 2.0, p =0.02), and voiding subdomains (3.5 versus 2.1, p <0.001) [35]. Interestingly, overall quality of life, uroflow Q max, and post-void residual were no different between groups.…”
Section: Hyperglycemia Insulin Resistance and Lower Urinary Tract Smentioning
confidence: 99%
“…International Prostate Symptom Score (IPSS) outcomes in patients with MetS were reported in 14 studies [5,6,8,[16][17][18][19][20][21][22][23][24][25][26][27]. There was statistically significant heterogeneity in these studies (…”
Section: International Prostate Symptom Scorementioning
confidence: 99%
“…A total of 7 studies investigated the role of MetS components on the risk of having moderate-to-severe LUTS [5,21,24,30,31,33]. The impact of waist circumference (WC) was showed in three studies [5,30,31].…”
Section: Mets Components and Risk Of Moderate-to-severe Lutsmentioning
confidence: 99%